Corrosion assisted the formation of unique structure transition metal oxides/carbon nanofibers with fast and high lithium storage. (20th December 2021) - Shi, Qian; Chen, Kaiyun; Xu, Minwei; Cheng, Yangqin; Tian, Fanghua; Yu, Zhonghai; Wang, Jingxiao; Dai, Zhiyong; Cao, Kaiyan; Zhang, Yin; Zhou, Xuan; Yang, Sen
Highlights: A facile method for synthesis of transition metal oxides/ carbon nanofibers @ transition metal oxides nanostructures through electrospinning, heat treatment, and corrosion. Co 3 O 4 /C nanofibers @ Co 3 O 4 nanosheets, ZnO/C nanofibers @ ZnO nanoparticles, and CuO/C nanofibers @ CuO nanoneedles are produced from this method showing excellent lithium-ion storage performance. Full cell tests of Co 3 O 4 /C nanofibers @ Co 3 O 4 nanosheets electrode also show high specific capacity and good cycle stability at high current density. Graphical abstract: Abstract: In this work, a facile and universal synthetic strategy is proposed to synthesize carbon nanofibers/ transition metal oxide composites with a three-dimensional cross-linked structure. The character of its morphology is the carbon nanofiber framework, based on which transition metal oxide nanoparticles and nanosheets (nanoparticles, nanoneedles) can be compounded inside and outside the nanofiber, respectively. The synthesis of this special morphology is achieved by electrospinning, heat treatment, and corrosion. By using this method, a series of hybrid materials including Co 3 O 4 /C nanofibers @ Co 3 O 4 nanosheets ( Co 3 O 4 /CFs @ Co 3 O 4 ), ZnO/C nanofibers @ ZnO nanoparticles (ZnO/CFs @ ZnO), and CuO/C nanofibers @ CuO nanoneedles (CuO/CFs @ CuO) can be successfully synthesized. The capacity of Co 3 O 4 /CFs @ Co 3 O 4 can reach 842.4 mAh g − 1 after 150 cycles, and ZnO/CFs @ ZnO and CuO/CFs @ CuO also show well cycle stability and high specific capacity as 650 mAh g − 1 and 544 mAh g − 1 after 600 cycles at 1 A g − 1 . This work can inspire the research of carbon nanofibers framework composite transition metal oxide nanostructure materials for outstanding lithium storage.